Headaches and hyperhidrosis: clinical features and outcomes after surgery - Peres, Mario Fernando Prieto; Brandão, Bianca Ferreira S.; Kauffman, Paulo; Campos, José Ribas Milanez de; Jatene, Fábio Biscegli; Wolosker, Nelson (Headache Medicine, 2010)
Both headache disorders and hyperhidrosis are debilitating conditions. Several primary headache syndromes have prominent autonomic features; the main therapeutic option for severe, focal hyperhidrosis addresses the autonomic system (thoracoscopic sympathectomy). Accordingly, herein we assessed headache outcomes in patients with hyperidrosis after sympathectomy. Sample consisted of 53 patients (43 women and 10 men) with hyperhidrosis and headaches. Headache clinical features and outcomes were assessed at baseline and after surgery. Mean age of sample was 27.1 years; 29 patients had palmar-plantar hyperidrosis, 17 had palmar-axillary, 9 had craniofacial and 4 had purely axillary hyperhidrosis. Twenty four (54.8%) patients had migraine; 20 (37.7%) had probable migraine and 4 (7.5%) had tension-type headache. Headache onset occurred after hyperhidrosis onset in 37 (69.8%) patients. Anxiety was reported by 94% of patients. Twenty four (45.3%) patients reported improvement of headache symptoms after surgery, 23 (43.4%) reported no change and 6 (11.3%) had worsening of symptoms after surgery. Overall headache frequency was significantly reduced after surgery, as contrasted to baseline. Hyperhidrosis may be comorbid to migraine, trough shared autonomic dysfunctions